PERPUSTAKAAN ISLAM CORDOBA: KIBLAT PERADABAN ILMU PENGETAHUAN DI ERA DINASTI BANI UMAYYAH II 961-976 M - Rahmat Iqbal; Agus Mahfudin Setiawan (Batuthah: Jurnal Sejarah Padaban Islam, 2024)
The Islamic Library in Cordoba was one of the leading libraries of its time, offering various fields of knowledge, including collections of Islamic and European history. This research aims to understand the development of scientific civilization which became a mecca of progress in Europe during the Second Umayyad Dynasty. This research methodology uses a library research approach with data collection through literature, documentation (both printed and electronic), as well as data and information sources relevant to the study. The findings in this study show that the development of science in Cordoba during the Second Umayyad Dynasty was driven by the construction of academies and libraries. The palace library in Cordoba, built by Caliph Abdurrahman, was one of the best libraries in the Islamic world at the time. It was staffed by a librarian called a "bakiya," and involved copyists and bookbinders. The glittering development of Islamic libraries during the Umayyad period had a great influence on the civilization of Arab society, making the Cordoba Library a center of advanced civilization in Europe. The existence of this library became the foundation for increasing knowledge and learning throughout the region, having a positive impact on civilization and culture at that time.